Full-field structured-illumination super-resolution X-ray transmission microscopy - Guenther, Benedikt; Hehn, Lorenz; Jud, Christoph; Hipp, Alexander; Dierolf, Martin; Pfeiffer, Franz (Nature Communications, 2019)
Modern transmission X-ray microscopy techniques provide very high resolution at low and medium X-ray energies, but suffer from a limited field-of-view. If sub-micrometre resolution is desired, their field-of-view is typically limited to less than one millimetre. Although the field-of-view increases through combining multiple images from adjacent regions of the specimen, so does the required data acquisition time. Here, we present a method for fast full-field super-resolution transmission microscopy by structured illumination of the specimen. This technique is well-suited even for hard X-ray energies above 30 keV, where efficient optics are hard to obtain. Accordingly, investigation of optically thick specimen becomes possible with our method combining a wide field-of-view spanning multiple millimetres, or even centimetres, with sub-micron resolution and hard X-ray energies.
CRIS-Team Scopus Importer:2023-03-08